Designing Supply Chain Resilience with a Quality Function Deployment Approach: A Case Study in a Shipping Line Company - Dira Ernawati; Isna Nugraha; Ni Ketut Sari (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Supply chain resilience is needed for companies to be able to reduce the impact of risks that can occur to the company. The purpose of this study is to analyze supply chain resilience in a shipping line company, which is one of the players in the maritime logistics industry. This research adopts a Quality Function Deployment (QFD) approach that considers customer needs and maritime risks. The results of this study identified 15 customer needs and obtained 3 priority customer needs, namely no errors on invoices and B/L, professional shipping services and easy and realtime tracking of goods shipments. 18 risks have been identified and 3 risk priorities have been obtained, namely damage to communication devices, handling errors and delays in handling documents or goods by EMKL. 26 causes of risk have been identified and 3 priority causes of risk have been identified, namely lack of skill and accuracy of employees, server disruption and lack of work motivation in employees. Based on the analysis that has been carried out in the previous sections, there are 18 resilience measures as risk mitigation that can be carried out by companies. The following are the top-ranked resilience measures, including providing training on sending and receiving goods, establishing good communication with customers and providing training on how to communicate well.